2012
DOI: 10.1007/s00122-012-1981-9
|View full text |Cite
|
Sign up to set email alerts
|

Anther extrusion and plant height are associated with Type I resistance to Fusarium head blight in bread wheat line ‘Shanghai-3/Catbird’

Abstract: Fusarium head blight (FHB) is a destructive wheat disease of global importance. Resistance breeding depends heavily on the Fhb1 gene. The CIMMYT line Shanghai-3/Catbird (SHA3/CBRD) is a promising source without this gene. A recombinant inbred line (RIL) population from the cross of SHA3/CBRD with the German spring wheat cv. Naxos was evaluated for FHB resistance and related traits in field trials using spray and spawn inoculation in Norway and point inoculation in China. After spray and spawn inoculation, FHB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
160
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(200 citation statements)
references
References 70 publications
36
160
4
Order By: Relevance
“…plant pathol. (2017) 42:165-174height was also found by Lu et al (2013). In that study, QTL common for both traits were associated with FHB resistance and interestingly one of the loci was Rht-B1.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…plant pathol. (2017) 42:165-174height was also found by Lu et al (2013). In that study, QTL common for both traits were associated with FHB resistance and interestingly one of the loci was Rht-B1.…”
mentioning
confidence: 55%
“…In addition, anthers and pollen partially trapped within the spikelet stimulate fungal growth and disease establishment compared to lines with rapid and complete anther extrusion. This relationship has been found and commented almost 100 years ago (Dickson et al 1921;Pugh et al 1933) and resurged recently as a focus of several research groups (Skinnes et al 2008(Skinnes et al , 2010Graham and Browne 2009;Kubo et al 2013;Lu et al 2013;He et al 2014;Buerstmayr 2015, 2016). Molecular-genetic analysis revealed a quantitative nature of anther retention/extrusion and detected the genetic basis for the phenotypic correlations with FHB traits.…”
Section: Morphological and Phenological Traitsmentioning
confidence: 83%
See 1 more Smart Citation
“…for genotype-by-year interaction, s 2 e for error variance, y for the number of years, and r for the number of replications (Lu et al 2013). In order to facilitate the identification of stably resistant lines, a composite index was calculated through the sixth root of the product of FHB index, FDK, and DON content in both 2013 and 2014.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In other studies, some wheat genotypes with high levels of anther extrusion tended to develop less FHB and had lower levels of DON (Skinnes et al 2010). Liu et al (2013) found that anther extrusion and plant height were negatively correlated with FHB severity. In summary, many researchers have reported that anthers play a critical role in FHB infection, but other research indicated there are other infection pathways including glumes (Tu 1930;cited in Kang and Buchenauer 2000), spikelets or rachis (Schroeder 1955;cited in Kang and Buchenauer 2000).…”
Section: Introductionmentioning
confidence: 74%